Juridical self and judicial review - Arachchi, I. (University of Colombo, 2025)
In this essay, I argue that every law operates on some prior assumptions about the subjects it seeks to govern and these assumptions together constitute the nature of that subject. I call this ‘the juridical self.’ As the current literature seems to treat the law as a phenomenon without a concept of the self on its own, conceptualization of the legal subject relies heavily on other branches of philosophy and even other disciplines. By contrast, the juridical self-rests on the argument that one does not need to look beyond the law to find an extra-legal version of self since the law is capable of providing the nature of its subjects - both fully and exclusively. Accordingly, a direct nexus between law and its subjects is not only possible to be drawn but is also necessary for a nuanced understanding of a legal system. The law in focus here is the judicial review of legislation. I argue that while the Constitutions and legislation encompass two different conceptions of the self, due to the scrutiny of legislation against the Constitution, the judicial review prefers the self under the Constitution over that under the legislation. This dichotomy between the Constitutions and legislation and the precedence of the former over the latter in a system of judicial review - as will be argued - is no coincidence but an upshot of a historic conflict between two rival conceptions of the self namely liberalism and communitarianism. In many modern democracies, the individualistic nature of the liberal self has been given effect to through a Constitutionalized Bill of Rights which – when enforced by the judiciary - is capable of silencing the underlying expectation of a statute that a person governed by it abides by the goals of his community although he may not necessarily agree with them.
Keywords: Juridical self; Judicial review; Constitution; Liberalism; Communitarianism